48th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2010
DOI: 10.2514/6.2010-71
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ipsilateral Wing-Wing Interactions on Aerodynamic Performance of Flapping Wings

Abstract: Dragonflies are masters of using the ipsilateral wing-wing interaction for different kinds of flying modes. It has been discovered that the phase difference between ipsilateral forewings and hindwings plays important role on wing aerodynamic performance. In the current study, we continue our research of a modeled dragonfly in slow flight (Liang and Dong (2009)) by varying the phase difference between the forewings and hindwings and look at the changes of aerodynamic performance of hindwings. Results of this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 13 publications
2
8
0
1
Order By: Relevance
“…Prior work with tandem flapping foils has also shown that for large enough spacing the forward foil is minimally affected by the presence of the aft foil [Boschitsch et al, 2014;Broering et al, 2012;Maybury and Lehmann, 2004]. Dong and Liang [2010] performed direct numerical simulation of a 3D dragonfly model at Reynolds number 216.5, and reported that the hindwings had minimal effect on the forewing performance; plots of thrust and lift versus time nearly overlay the forewing results with and without the presence of the hindwing, for three inter-foil phase angles. Maybury and Lehmann [2004] performed an experiment using a dragonfly model at Re = 100, with fore-and hindwings spaced at s/c = 5.…”
Section: Effect Of the Aft Foil On The Forward Foilmentioning
confidence: 96%
“…Prior work with tandem flapping foils has also shown that for large enough spacing the forward foil is minimally affected by the presence of the aft foil [Boschitsch et al, 2014;Broering et al, 2012;Maybury and Lehmann, 2004]. Dong and Liang [2010] performed direct numerical simulation of a 3D dragonfly model at Reynolds number 216.5, and reported that the hindwings had minimal effect on the forewing performance; plots of thrust and lift versus time nearly overlay the forewing results with and without the presence of the hindwing, for three inter-foil phase angles. Maybury and Lehmann [2004] performed an experiment using a dragonfly model at Re = 100, with fore-and hindwings spaced at s/c = 5.…”
Section: Effect Of the Aft Foil On The Forward Foilmentioning
confidence: 96%
“…The high rolling amplitude did not appear to improve the thrust but could reduce the power losses. In another experimental study, Bandyopadhyay et al [11] explored low-aspect-ratio flapping fins (AR=3) at chord Reynolds numbers between 3 3.6 10  and 5 1.5 10  in a tow tank. The authors demonstrated that low-aspect-ratio pitchingrolling fins can only produce thrust within a bounded Strouhal number (0.2<St<1.5) and that their optimal efficiency can be achieved by tailoring the Strouhal number and pitch amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…LAPPING motion is widely utilized by many kinds of biological propulsors, including fish pectoral fins [1,2] and insect/bird wings [3,4,5]. The inherently unsteady nature of flapping kinematics is responsible for the primary force production, and also differentiates flapping-wings motion from conventional fixed-and rotary-wing configurations.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation on the tandem wings is motivated by the design of quad-wing MAVs that mimic dragonfly or damselfly flight due to their superior performance in maneuver and endurance [4][5][6][7] . The effect of complex wake structures produced by the tandem wings has been studied experimentally [8] and numerically [9][10][11][12] . These researches provide great insight into the flow physics such as wing-wake interaction, vortex formation and vortex shedding, and assist the development of more comprehensive aerodynamic models.…”
Section: Introductionmentioning
confidence: 99%